MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR PENDIDIKAN PANCASILA PESERTA DIDIK KELAS VI SDN TAMBAN RAYA BARU DENGAN MENGGUNAKAN MODEL MOUNTAIN DAN PERMAINAN ULAR TANGGA - Fatihah, Dea Amani; Herti Prastitasari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study reviews the lack of student activity and learning achievement due to the less varied teaching and learning methods, assignments that are not based on HOTS and lack of understanding of Pancasila Education material. The solution to these problems is to make improvements through the application of the GUNUNG model and the snakes and ladders game. This study aims to describe teacher actions, analyze changes in student behavior and student learning outcomes. This study uses the Classroom Action Research method with the target of the research being 24 sixth grade students of SDN Tamban Raya Baru. This study uses qualitative and quantitative data. Qualitative data are obtained by observing the activities of teachers and students, while quantitative data in the form of classical percentages of student activities and student learning outcomes are obtained from group and individual tests. The results of this study prove that teacher activity at meeting IV meets the criteria of